Foundations of a planned economy 1926-1929 - Carr, Edward Hallett; Davies, R.W. (Harmondsworth : Penguin Books, 1974)
Bibliotheek François Vercammen
Engels
Meerdelige publicatie
Keywords: planeconomie; Sovjet-Unie.